Teacher talk focusing on instructions in university english classes - Aziyanawati, Mohamad Othman. (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study aims to identify the types of teaching instructions that frequently used by the instructor in university English classroom based on the teacher talk being used in their lecture session. Teaching instructions refer to the way teacher teaches the curriculum. This is the important element to help the students to get the knowledge and learn from the teacher. However, there is little research done on teaching instructions specifically used by instructor in university English classroom. Therefore, this research attempts to find out the types of teaching instructions used and how English instructor manages instruction in University English classroom. The study involved three instructors of Preparatory English 2 course. Data were obtained from audio observation of Preparatory English 2 classes. The transcriptions of the recordings were analysed based on framework of Ornstein & Lasley II (2004) on the types of teaching instructions. The finding shown that the most popular teaching instructions used by the instructors are lecturing, questioning, giving direction and practice and drill. The researcher also found that, the instructors used and incorporated that teaching instructions in their lecture sessions for certain reasons or purposes.